Asam pop: let it pop / Mohamad Khairolnazmi Khairudin ... [et al.] - Khairudin, Mohamad Khairolnazmi; Rozli Sam, Muhammad Haziq; Hamidi, Mohamad Hazim; Abdullah, Ameerul Haziq; Md. Yunus, Akmal Danial; Sazali, Khairul Zahin
Asam Pop involves in manufacturing 'asam' powder, we will make sure that our customers will get only the high quality 'asam' powder which are from our own recipes. After doing some research, we conclude that there is a high demand of our products from the people. Therefore, we see this as an advantage to grab the opportunity of making profit. We only provide products that are fresh and halal for our customers and it is our pleasure to satisfy their needs and wants. As conclusion, we are sure that we are able to cater to the needs and wants of our target market. We hope that we can be the main 'asam' powder manufacturer not only in Johor but also in Malaysia. Furthermore, we also hope that our products can enter the international market in years ahead. We will give all of our efforts to make this hope comes true.